European Corn Borer, Ostrinia nubilalis (Hubner) (Insecta: Lepidoptera: pyralidae) - John L. Capinera (EDIS)
This document is EENY-156, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2000.